2002
DOI: 10.1177/153944920202200103
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factor Structure and Psychometric Properties of the Test of Visual-Perceptual Skills

Abstract: This study examines psychometric properties and factor structure of the Test of VisualPerceptual Skills (nonmoior) (TVPS), a measure developed to assess children with schoolrelated learning difficulties. Following a descriptive retrospective study design, clinic record data were compiled for a convenience sample of 294 children. While measure usewas generally supported, findings indicate areas wherein themeasure lacks psychometric soundness. Item analysis using point biserial correlations showed a low relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Klein, Sollereder and Gierl (2002) identified reliability issues when they calculated Cronbach's alpha with 294 children aged 6 to 12 years for the unrevised version of the "Test of Visual-Perceptual skills". The…”
Section: Judging Reliability Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Klein, Sollereder and Gierl (2002) identified reliability issues when they calculated Cronbach's alpha with 294 children aged 6 to 12 years for the unrevised version of the "Test of Visual-Perceptual skills". The…”
Section: Judging Reliability Estimatesmentioning
confidence: 99%
“…The sample size might also influence reliability estimates. Klein, Sollereder & Gierl (2002) identified reliability issues when they calculated Cronbach's alpha with 294 children aged 6 to 12 years for the unrevised version of the 'Test of Visual-Perceptual Skills'. The alpha of each subtest for each age group ranged between 0.23 and 0.89.…”
Section: Cronbach's Alpha In Paediatric Occupational Therapy Assessmentmentioning
confidence: 99%
“…0-0.25 = little, 0.26-0.49 = low, 0.5-0.69 = moderate, or >0.7 = high (Kline, 1986;Munro, 1997). If a unidimensional factor adequately describes each subscale, the factor loading for the observed construct would be large (>0.35) (Brown & Gaboury, 2006;Klein, Sollereder, & Gierl, 2002).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 98%
“…This includes a wide range of item passing rate (between .35 and .96) (Gardner), high internal consistency (Cronbach's alpha between .83 to .91) (Gardner) and small standard error of measurement (SEM ) (between 4.48 to 6.20) (Gardner). A lack of gender bias (Gardner), low to moderate intersubtests correlation (between .18 to .51) (Klein, Sollereder & Gierl, 2002), moderate to high subtest-total correlation (between .59 to .76) (Klein et al), and low to moderate correlation with intellectual tests (between .37 to .52) and visual-motor tests (.42) (Klein et al) were also reported.…”
mentioning
confidence: 95%
“…In addition to the lack of item-level information available, a few other areas deserve attention. First, the studies of both Klein et al (2002) and McFall et al (1993) were conducted on children 6 years of age or older, but not on younger children who were likely to be more difficult to test reliably as they were less able to concentrate or to follow instructions (Sattler, 1992). Second, although the test results were shown to be lower in children with learning disabilities (Gardner, 1996), the known-group comparison had not been investigated on children with identified visual-perceptual difficulties.…”
mentioning
confidence: 99%